Solid Lipid Nanoparticles (SLN) and Nanostructured Lipid Carriers (NLC) Prepared by Microwave and Ultrasound-Assisted Synthesis: Promising Green Strategies for the Nanoworld - Karla L. López; Andrea Ravasio; José Vicente González-Aramundiz; Flavia C. Zacconi (MDPI AG, 2023)
Many pharmaceutically active molecules are highly lipophilic, which renders their administration and adsorption in patients extremely challenging. Among the countless strategies to overcome this problem, synthetic nanocarriers have demonstrated superb efficiency as drug delivery systems, since encapsulation can effectively prevent a molecules' degradation, thus ensuring increased biodistribution. However, metallic and polymeric nanoparticles have been frequently associated with possible cytotoxic side effects. Solid lipid nanoparticles (SLN) and nanostructured lipid carriers (NLC), which are prepared with physiologically inert lipids, therefore emerged as an ideal strategy to bypass toxicities issues and avoid the use of organic solvents in their formulations. Different approaches to preparation, using only moderate amounts of external energy to facilitate a homogeneous formation, have been proposed. Greener synthesis strategies have the potential to provide faster reactions, more efficient nucleation, better particle size distribution, lower polydispersities, and furnish products with higher solubility. Particularly microwave-assisted synthesis (MAS) and ultrasound-assisted synthesis (UAS) have been utilized in the manufacturing of nanocarrier systems. This narrative review addresses the chemical aspects of those synthesis strategies and their positive influence on the characteristics of SLNs and NLCs. Furthermore, we discuss the limitations and future challenges for the manufacturing processes of both types of nanoparticles.